(untitled) (The Harvest, 2023)
This study aims to analyze determinants of stock price of Nepalese commercial banks. The study is conducted by using quantitative method followed by descriptive research to make brief and accurate study on selected variables and pooled cross-sectional data that are collected from NEPSE listed banks at one point in time. The data are collected covering the period from the F/Y 2011/12 to 2020/21. Ten commercial banks are selected as representative of target population of 26 commercial banks. The research variables are book value per share, PE ratio, firm size, dividend payment, return on equity and market price per share. Under the statistical analysis, descriptive statistics, correlation and multiple regression analysis are conducted. Descriptive statistics shows the book value per share and firm size of Nepalese commercial banks have been found steadily growing whereas the profitability, dividend and stock performance in market are quite volatile. The P/E ratio is found to be nil in some of the year due to no earnings per share of particular bank. Share price of Nepalese commercial banks is positively correlated to BVPS, PE, ROE and DIV whereas negative relationship with firm size (FS). Among the independent variables, all variable except firm size (FS) are statistically significant. Regression results reveals that BVPS, PE, ROE and DIV have positive and significant impact on MPS whereas firm size (FS) has significant and negative impact on MPS.